2019
DOI: 10.15766/mep_2374-8265.10854
|View full text |Cite
|
Sign up to set email alerts
|

Using an Entrustable Professional Activity to Assess Consultation Requests Called on an Internal Medicine Teaching Service

Abstract: Introduction:The Accreditation Council for Graduate Medical Education's milestones require internal medicine residents to have competency in calling consults. Based on a literature review, we developed an Entrustable Professional Activity (EPA) to delineate the knowledge, skills, and attitudes required for a consultation request and, building on the EPA, implemented an assessment instrument to provide feedback to interns calling consultation requests and assess the quality of their consult questions and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A one-year longitudinal study conducted by Ju et al, found that after the implementation of EPAs, physicians showed enhanced confidence levels[ 27 ]. Kang et al found that there is strong positive association between the resident’s appraisal of the intern’s competence to how well they use EPAs framework[ 28 ]. After the implementation of EPAs, most participants were aware of the required criteria for summative entrustment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…A one-year longitudinal study conducted by Ju et al, found that after the implementation of EPAs, physicians showed enhanced confidence levels[ 27 ]. Kang et al found that there is strong positive association between the resident’s appraisal of the intern’s competence to how well they use EPAs framework[ 28 ]. After the implementation of EPAs, most participants were aware of the required criteria for summative entrustment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…EPAs have been developed by other medical specialties such as pediatrics, internal medicine, surgery, psychiatry, and family medicine, among others. 1,[5][6][7][8][9][10][11][12] These EPAs are specific for each specialty or subspecialty but have common themes such as being able to provide consultation and competence in performing procedures and providing appropriate clinical care. Until recently, it was typical for just pathology/transfusion medicine and nephrology trainees to undergo apheresis rotations or demonstrate proficiency in apheresis procedures during their graduate or postgraduate medical education.…”
Section: Discussionmentioning
confidence: 99%
“…EPAs have been developed by other medical specialties such as pediatrics, internal medicine, surgery, psychiatry, and family medicine, among others 1,5–12 . These EPAs are specific for each specialty or subspecialty but have common themes such as being able to provide consultation and competence in performing procedures and providing appropriate clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations